The past has another pattern - Ball, George W. (Norton and Company, 1982)
In his long and multifaceted career as a diplomat, international lawyer, and statesman, George W. Ball has been at the center of many crises. His book is filled with candid portraits of major figures on the world stage, as well as keen and controversial insights into past and present international problems